(untitled) (Papeles, 2017)
Mathematics has been generally recognised as one of the most complex areas of knowledge. In many cases, people believe that a student’s performance on this area exerts a great influence over the degree, or at least, the area of knowledge a student chooses to major once he graduates from High School. This academic paper intends to research the level of correlation between a student’s degree choice and his performance in mathematics. The reference frame will be a group of students from different faculties of the Universidad Nacional de Colombia, who will be surveyed about the degree they are majoring in and their performance in Mathematics in the state exam “Saber 11” (ICFES).